Guidelines for the Management of Hypertension in Nigeria (2020)
Background: Hypertension, defined as blood pressure > 140/90 mmHg, has assumed greater public health importance in Nigeria in the last 2 decades. Many reports put the adult prevalence rates at 20-40%, with some major ones specifically reporting 27.8% and 28.9%. Low detection and reporting rates, inadequate investigation and treatment rates all combine to increase the burden. The guidelines provide updated information. Recommendations: The traditional risk factors, with the addition of high income and education status, are highlighted. Recommendations regarding the use of devices and the setting, including home and ambulatory, in the measurement of the blood pressure, are updated. The importance of total cardiovascular risk assessment and risk stratification, employed in initiating and guiding therapy, is emphasized. Lifestyle modifications are prescribed for all; they are described with estimates of BP responses and with a greater reference to local conditions. Attention is drawn to the early use of medicine therapy in those with high CV risk and multi-medicine therapy in those with BP > 160/100 mmHg. The use of single pill combinations, wherever feasible, is recommended, and the prediction is made of most patients eventually requiring multi-medicine therapy. Considerations of cost, availability, tolerance and patient-specific factors influence the choice of medicines, and although any of the several medicine classes could be used for initial therapy, thiazide and thiazide-like diuretics and calcium channel blockers are recommended for single or dual-medicine therapy. Alternatively, any of these and any of angiotensin converting enzyme inhibitor, angiotensin receptor blocker, centrally acting agent, beta-blocker or alphablocker could be used for combination therapy. Effective and recommended combinations and a list of the commonly available medicines in Nigeria are listed. Aspirin for secondary prevention and statin therapy should be used as required. The goal of treatment is commonly <140/90 mmHg, but could be lower in patients with diabetes, chronic kidney disease. Patient counselling, follow-up and treatment monitoring are emphasised. Outlines of treatment in special groups or situations including diabetes, chronic kidney disease, haemoglobinopathies, HIV-infection, paediatric patients, patients with sexual dysfunction, resistant hypertension, hypertension emergency, community control and prevention are provided.